USING OF SPECIALIZED SOFTWARE IN MODELING OF THROWING INTO THE BASKET HOOP - Virgil Larionescu Moroşan; Alexandru Ciobara (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The necessity of developing the most efficient learning models adapted to the current society is part of a permanent desire of the specialists in the field, which is no longer possible without a thorough analysis using more and more specialized software and cameras, that can surprise those acts that can easily "escape" from our attention due to the speed of action or complexity of the movement.